Calculating with letters: Computing with letters
Factorisation of a quadratic polynomial via the sum-product method
A quadratic equation in the variable \(x\) is an expression of the form \[ax^2+bx+c=0\] for certain numbers \(a\), \(b\), and \(c\) with \(a\neq0\). The basic form of the sum-product method assumes \(a=1\).
The sum-product method
In the sum-product method, also called product-sum-method or factorisation by inspection, we try to factorise \(x^2+b\,x+c\) as \((x+p)(x+q)\) for certain \(p\) en \(q\). If you expand brackets in the factored form, then we get \[x^2+b\,x+c=x^2+(p+q)x+p\times q\text.\] Therefore, the task has become to find two numbers \(p\) and \(q\) such that \[p+q=b\quad\mathrm{and}\quad p\times q=c\]
Examples
\[x^2+3x+2=(x+1)(x+2)\] because \(1+2=3\) and \(1\times 2=2\).
\[x^2-x-12=(x-4)(x+3)\] because \(-4+3=-1\) and \(-4\times 3=-12\).
\(x^2+5x + 4={}\)\((x+1)(x+4)\).
We try to find integers \(p\) and \(q\) such that \(x^2+5x + 4=(x+p)(x+q)\).
Expansion of brackets in the right-hand side then gives: \[x^2+5x + 4=x^2+(p+q)x+p\times q\] So we try to find integers \(p\) and \(q\) so that \(p+q=5\) and \(p \times q= 4\).
Because we may interchage \(p\) and \(q\) it suffices to choose \(p\) such that \(p^2\le 4\),
i.e., choosing \(p\) with \(|p|\le\sqrt{4}=2\).
We make a table of possibilities integers: \[\begin{array}{||r|r|r||} \hline p & q & p+q\\ \hline 1 & 4 & 5\\ \hline -1 & -4 & -5\\ \hline 2 & 2 & 4\\ \hline -2 & -2 & -4\\ \hline \end{array}\] \(p=1\) and \(q=4\) meet the requirements.
The factorisation is: \[x^2+5x + 4=(x+1)(x+4)\]
We coupled the sum-product method to quadratic polynomials, but sometimes they are in disguise within the algebraic expressions. The examples below illustrate this.
\(t^{6}-t^{5} -2t^4={}\)\(t^4(t-2)(t+1)\).
Note first that all terms can be divided by \(t^4\) so that \[t^{6}-t^{5} -2t^4=t^4(t^2-t -2)\] and that the quadratic polynomial between the brackets is in the form in which the product-sum method with integer coefficients is applicable.
Next we try to find integers \(p\) and \(q\) such that \(t^2-t -2=(t+p)(t+q)\).
Expansion of brackets in the right-hand side then gives: \[t^2-t -2=x^2+(p+q)t+p\times q\] So we try to find integers \(p\) and \(q\) so that \(p+q=-1\) and \(p \times q= -2\).
Because we may interchage \(p\) and \(q\) it suffices to choose \(p\) such that \(p^2\le 2\),
i.e., choosing \(p\) with \(|p|\le\sqrt{2}\approx 1.414\).
We make a table of possibilities integers: \[\begin{array}{||r|r|r||} \hline p & q & p+q\\ \hline 1 & -2 & -1\\ \hline -1 & 2 & 1\\ \hline \end{array}\] \(p=-2\) and \(q=1\) meet the requirements.
The factorisation is: \[t^2-t -2=(t-2)(t+1)\] The final result is: \[t^{6}-t^{5} -2t^4=t^4(t-2)(t+1)\]
Mathcentre video
Factorization of a Quadratic Equation by Inspection (42:36)